Anticancer Molecules from Catharanthus roseus - Zarani M Taher; Farid Agouillal; Lim J. R; Aina Q Marof; Daniel Joe Dailin; Muktiningsih Nurjayadi; Ezzaty NM Razif; Sara E Gomaa; Hesham Ali El Enshasy (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2019)
Catharanthus roseus is an important medicinal plant found in various parts of the world and the bioactive compound has been extracted and used as anti-cancer agent to treat the cancer over decades. However, the extraction of bioactive compound also results in the generation of large quantities of pollution with wasted solvents. Toxic pollution occurs when synthetic chemicals are discharged or natural chemicals accumulate to toxic levels in the environment, causing reductions in wildlife numbers, degrading ecosystem functions and threatening human health. This review covers the extraction and phytochemical obtained leading to chemical compounds related to anti-cancer property of C. roseus. Additionally, recent advances of using biological cell cultures were also addressed. Thus, this work can be used for further investigation of C. roseus to be undertaken in future for its anti-cancer property further development and efficient production in drug industry